التحديات والإشكالات التي تواجه تطبيق صيغة الوقف المؤقت في ولايات مختارة في ماليزيا الصور المستحدثة وضوابطها = Challenges and problems facing the application of temporary Waqf in selected states in Malaysia: new issues and their guiding rules - Ab Rahman, Muhamad Firdaus; Amanullah, Muhammad Amanullah (King Abdulaziz University Scientific Publishing Center, 2017)
This paper aims to critically examine challenges of the application of temporary waqf in selected states of Malaysia, to establish principles and to suggest new approaches for its implementation. A qualitative methodology was employed to analyse the data through inductive, deductive and field research methods. As for the field research, this study has conducted semi-structured interviews with the Waqf Corporations and Mufti`s Department in the selected states of Malaysia, namely; Selangor, Malacca, Negeri Sembilan and Johor. The result shows that inappropriate procedures of fatwa issuance, unproductive current waqf assets and legal perspective issues are among the challenges in implementing temporary waqf in Malaysia. Thus, this paper proposes that every State’s Waqf Corporations in Malaysia should reassess the existing legal framework of temporary waqf in order to realize its application as an effective solution for the current waqf properties. Finally, the study proposes to establish holistic principles of temporary waqf implementation in Malaysia.